2002
DOI: 10.1017/s1355770x02000153
|View full text |Cite
|
Sign up to set email alerts
|

Green national accounting: the case of Chile's mining sector

Abstract: This article uses the welfare foundations for the usual net domestic product (NDP) income measure of the traditional National Accounts System (NAS) provided by Weitzman (1976Weitzman ( , 2000, and the propositions of Hartwick (1993) andHamilton (1994a) to correct this measure in order to obtain a green (sustainable) measure of economic income. It estimates green measures of the economic income of Chile's mining sector for the period 1977-1996. Different methodologies regarding the valuation of mining resources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Thus in Chile, one of the banner countries for the ‘mining leads to development’ argument, conventional accounting measures suggest that mining contributed between 7 and 9 per cent of the country's GDP during the first half of the 1990s. However, environmental economists from the University of Chile and Chile's National Commission for the Environment concluded that such accounting methods ‘overestimated the economic income generated by the Chilean mining sector… by 20–40 per cent’ (Figueroa et al, 2002: 215), even when only factoring in the costs of resource depletion. Had additional environmental and health effects of mining, such as air or water pollution, also been included then the overestimation would have been greater still.…”
Section: Curses Conflicts Contaminations: Debating the ‘Paradox Of mentioning
confidence: 99%
“…Thus in Chile, one of the banner countries for the ‘mining leads to development’ argument, conventional accounting measures suggest that mining contributed between 7 and 9 per cent of the country's GDP during the first half of the 1990s. However, environmental economists from the University of Chile and Chile's National Commission for the Environment concluded that such accounting methods ‘overestimated the economic income generated by the Chilean mining sector… by 20–40 per cent’ (Figueroa et al, 2002: 215), even when only factoring in the costs of resource depletion. Had additional environmental and health effects of mining, such as air or water pollution, also been included then the overestimation would have been greater still.…”
Section: Curses Conflicts Contaminations: Debating the ‘Paradox Of mentioning
confidence: 99%
“…This in spite that resource depletion should be valued using the long run equilibrium net price resulting from an intertemporal maximization process. However, the approach followed by Gómez-Lobo (1991), Nuñez (1992), and Figueroa et al (2002) is employed here, valuing with a unit rent of a base year. The unit rent (net price) for each natural resource included was calculated from the data of the 1986 Input-Output Matrix, according to the following formula:…”
Section: Estimation Of True Economic Income and Genuine Saving For Chilementioning
confidence: 99%
“…The study showed that the standard approach overestimated the income generated by the Chilean mining sector during the period by between 20 and 40 per cent, and its rate of growth by between 3 and 20 per cent. Moreover, the bias was similar for the different methodologies used (Figueroa et al, 2002). There have also been studies of the effect of including positive production externalities.…”
Section: Valuing Environmental Externalities and Environmental Assetsmentioning
confidence: 74%